Desafíos de las políticas públicas para enfrentar el proceso del envejecimiento de la población mexicana (Challenges of the public policies to handle Mexican population’s aging process) - Moreno, M.G.; Badii Zabeh, Mohammad Hosein (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. The aging of the population poses an emergent problem for our country by its multiple repercussions. Between the aspects more worrying are found the sanitary situation and the gender inequity. Considering it previous, the present article has as initial purpose points out any information concerning ciphers that show the demographic aging in our country. Subsequently, the sanitary situation is raised and the conditions of health of old age; as well as some differences according to the gender. This information is used as framework of reference for the reflection concerning factors that have influenced negatively for that the conditions are not optima in this stage of the life. Finally, some strategies are proposed oriented to improve the quality of life of old age.